Pemaparan Krisis Identiti dalam Karya Pengarang Malaysia dan Indonesia: Satu Perbandingan - Rahimah Haji A Ahmad (HISKI, 2006)
During and after British Colonialism in Malaysia, as well as Dutch colonialism in Indonesia, many colonial subjects, especially the natives, have experienced an identity crisis. According to Linda Martin Alcoff (2000:324), since almost two decades ago, identity crisis has sparked a heated debate in psychoanalysis, poststructuralism and postcolonial studies. Specifically in postcolonial studies, identity crisis has clearly become a fundamental problem of people in the colony, considering that colonization by foreign power took place over a very long span of time.Prolonged colonization may have caused a colonized country, nation, or individual suffer from a contaminated identity as they have been co-opted and dominated by the culture of their colonizer, which was usually considered stronger, bigger, and more powerful. Then, as national consciousness began to emerge among the colonized, particularly after independence, once again they began to embark on the quest for a national and individual identity. However, what they mostly encountered is natives whose identity is fracture and shaped by double consciousness. Such an identity comes into being due to the long period of colonization, which helped institutionalize various colonial practices that had only served to dominate the natives and maintained unequal power relations.There are two determining factors that cause the natives to experience identity crisis. First, they were led to believe that they were inferior and taught to cultivate self-hatred. At the same time, they were also made to worship Western civilization. Second, colonialism brought about chronic moral degradation among the natives.Viewed from this perspective, some Malaysian and Indonesian native writers take on identity crisis as the theme of their works. Authors such as Keris Mas, Abdul Moeis and Mochtar Lubis will be examined using a comparative approach. The purpose of this study is to raise awareness among the natives in both countries in general and in the HISKI community in particular to maintain their independence. Independence is key to help the natives deal with any threat to the survival of their identity brought about by identity crisis. Actually, the selected works of these authors are a reflection of the past history of the people in the colony, which allows the present-day generation to draw a lesson from it so that the impact of colonialism may not linger forever.